2023
DOI: 10.2147/jir.s428641
|View full text |Cite
|
Sign up to set email alerts
|

Clinical Significance of Mean Platelet Volume Combined with Neutrophil–Lymphocyte Ratio in Predicting the Therapeutic Effect of Splanchnic Neurolysis

Junzhu Dai,
Yuxiang Han,
Tianyi Fang
et al.

Abstract: In most cases of pain related to abdominal tumors, increasing the dosage of analgesics still makes the pain difficult to alleviate. Splanchnic neurolysis is a new treatment option. However, not all patients receiving splanchnic neurolysis treatment will achieve satisfactory results. The aim of this study is to retrospectively analyze the predictive value of preoperative serum immune indicators (white blood cells, neutrophils, lymphocytes, and platelets) for the efficacy of splanchnic neurolysis. Methods: The a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

0
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 32 publications
(38 reference statements)
0
1
0
Order By: Relevance
“…
We recently with great interest read the report from Dai et al 1 Their study aimed to retrospectively analyze the predictive value of mean platelet volume (MPV) combined with the neutrophil-lymphocyte ratio (NLR) for the efficacy of splanchnic neurolysis. The results revealed that MPV has statistical significance for predicting splanchnic neurolysis efficacy in digestive system tumors.
…”
mentioning
confidence: 99%
“…
We recently with great interest read the report from Dai et al 1 Their study aimed to retrospectively analyze the predictive value of mean platelet volume (MPV) combined with the neutrophil-lymphocyte ratio (NLR) for the efficacy of splanchnic neurolysis. The results revealed that MPV has statistical significance for predicting splanchnic neurolysis efficacy in digestive system tumors.
…”
mentioning
confidence: 99%